Percepções de professores-cursistas sobre um curso de inglês mediado por computador - Nogueira, Luciana Costa (2009)
The objectives of this study are: to analyze how the teaching-learning theories and language descriptions that ground the Brazilian National Curriculum Parameters to teach foreign languages in elementary and secondary schools (PCN-LE, Brasil, 1998 and PCN-EM, Brasil, 1999) are present in a computer-mediated English course called Interaction Teachers; and to identify the perceptions of teachers, participants of this course, on linguistic and technological aspects exploited in it. This research is grounded on concepts discussed in the Brazilian National Curriculum Parameters to teach foreign languages in elementary and secondary schools (PCN-LE, Brasil, 1998 and PCN-EM, Brazil, 1999) as well as on currents of thoughts in psychology that form the basis for teaching-learning theories that have most influenced the teachinglearning of foreign languages in our culture (Williams & Burden, 1997, Vygotsky, 1934/2007). This study is also based on concepts of language descriptions (Hutchinson & Waters, 1987; Nunan, 1999), principles of Computer-Assisted Language Learning -- CALL (Warschauer & Healey, 1998, 2004, Beatty, 2003; Hardisty & Windeatt, 1989) and the criteria for didactic material evaluation proposed by Ramos (1998). This study, a case study, was conducted with six student-teachers. The data were collected in 2008, by questionnaires. The analysis of the course shows that the language description and the teaching-learning theory that underlie the course Interaction Teachers do not match the paradigms in the Brazilian National Curriculum Parameters to teach foreign languages in elementary and secondary schools (PCN-LE, Brasil, 1998 and PCN-EM, Brazil, 1999) because the course is based on the structural view of language and on the behaviorist teachinglearning theory. As far as the participants perceptions on linguistic and technological aspects exploited in the course are concerned, results show that they have not improved either their linguistic knowledge or technological skills as a consequence of attending the course